A Novel Insight into the Immunologic Basis of Chronic Granulomatous Invasive Fungal Rhinosinusitis. Issue 2 (June 2016) - Rae, William; Doffinger, Rainer; Shelton, Fenella; Sproson, Eleanor; Ismail-Koch, Hasnaa; Lund, Valerie J.; Harries, Philip G.; Eren, Efrem; Salib, Rami J.
Background: Chronic granulomatous invasive fungal rhinosinusitis (CGIFRS) is a rare disease. The underlying immune responses that drive the development of CGIFRS, as opposed to successful pathogen clearance and controlled inflammation, are not currently known. Objective: To characterize the immune responses associated with CGIFRS. Methods: In addition to a battery of basic investigations, more in-depth immunologic testing involves ex vivo whole-blood stimulation with the polyclonal T-cell mitogen phytohemagglutinin and fungal antigens with interleukin (IL) 12, was undertaken to investigate cell-mediated immune responses associated with CGIFRS. Results: Ex vivo whole-blood stimulation with the polyclonal T-cell mitogen phytohemagglutinin and fungal antigens with IL-12 identified reduced interferon gamma and increased IL-17A levels within the supernatant, which indicated increased in vivo T-helper (Th)17 responses and impaired Th1 responses compared with healthy controls. Conclusion: These findings suggest that the development of CGIFRS may be associated with an abnormally exaggerated host Th17 response, which caused failure to clear the fungal pathogen with refractory fungal infection of mucosal membranes, resulting in chronic tissue inflammation.